2019
DOI: 10.1136/bmjopen-2019-029879
|View full text |Cite
|
Sign up to set email alerts
|

How reliable is perioperative anticoagulant management? Determining guideline compliance and practice variation by a retrospective patient record review

Abstract: ObjectivesSurgery in patients on anticoagulants requires careful monitoring and risk assessment to prevent harm. Required interruptions of anticoagulants and deciding whether to use bridging anticoagulation add further complexity. This process, known as perioperative anticoagulant management (PAM), is optimised by using guidelines. Optimal PAM prevents thromboembolic and bleeding complications. The purpose of this study was to assess the reliability of PAM practice in Dutch hospitals. Additionally, the variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…However, the makeup of patients in this clinic appears representative in terms of clinical indications for anticoagulation (i.e., AF > VTE > MHV) as other anticoagulation clinic settings. 19 20 Moreover, the surgeries/procedures patients underwent, with the majority being low-/moderate-bleed-risk surgeries/procedures, are consistent with that observed in studies involving unselected patients who are receiving a DOAC or VKA. 5 7 8 Third, we may have underestimated the proportion of patients who require heparin bridging as this was limited to warfarin-treated patients with an MHV and we did not include warfarin-treated patients with AF or VTE.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, the makeup of patients in this clinic appears representative in terms of clinical indications for anticoagulation (i.e., AF > VTE > MHV) as other anticoagulation clinic settings. 19 20 Moreover, the surgeries/procedures patients underwent, with the majority being low-/moderate-bleed-risk surgeries/procedures, are consistent with that observed in studies involving unselected patients who are receiving a DOAC or VKA. 5 7 8 Third, we may have underestimated the proportion of patients who require heparin bridging as this was limited to warfarin-treated patients with an MHV and we did not include warfarin-treated patients with AF or VTE.…”
Section: Discussionsupporting
confidence: 73%
“…It is possible that a virtual model of care would be less applicable, for example in clinics that assess predominantly patients with a MHV in whom heparin bridging may be more widely used. However, the make-up of patients in this clinic appears representative in terms of clinical indications for anticoagulation (i.e., AF > VTE > MHV) as other anticoagulation clinic settings 19,20 . Moreover, the surgeries/procedures patients underwent, with the majority being low/moderate-bleed-risk, is consistent with that observed in studies involving unselected patients who are receiving a DOAC or VKA 5,7,8 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Previous studies on noncompliance with perioperative anticoagulation management guidelines have shown poor compliance, similar to the results found in our study [ 19 – 22 ]. Moesker et al described guidelines compliance of 40–81%, depending on the step of the perioperative anticoagulation management [ 21 , 22 ]. Contrary to our study, they found that the incidence of guidelines noncompliance was highest in the postoperative steps when VKA therapy was reinitiated.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was confirmed with our ordinal logistic regression analysis (Table 5) that predicted a positive association of more than 24‐fold between physicians' non‐adherence to evidence‐based guidelines and the medication error severity compared to the full or partial adherence group. While no studies investigated physician adherence to guidelines as a predictor of the incidence and severity of medication errors, Moesker et al 29 concluded that physician adherence to perioperative anticoagulant management guidelines is “suboptimal”, which leads to increased risk of adverse events inflicted upon patients, and recommended further procedures to increase physician compliance. Haque and his colleagues 30 reported a necessity to help healthcare providers adhere to direct oral anticoagulant guidelines through prescribing aid tools.…”
Section: Discussionmentioning
confidence: 99%